2013
DOI: 10.3389/fpls.2012.00311
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic responses of fruits to environmental stresses

Abstract: Fruits and vegetables are extremely susceptible to decay and easily lose commercial value after harvest. Different strategies have been developed to control postharvest decay and prevent quality deterioration during postharvest storage, including cold storage, controlled atmosphere (CA), and application of biotic and abiotic stimulus. In this review, mechanisms related to protein level responses of host side and pathogen side were characterized. Protein extraction protocols have been successfully developed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 97 publications
0
17
1
Order By: Relevance
“…The proteins present in the mesocarp of fleshy fruits tend to be associated with the metabolic processes of the plant, environment and the stress of pathogen exposure. When plants are subjected to different environmental stresses, qualitative and quantitative changes in the protein content occur [23]. This phenomenon could explain the levels of total proteins found in the pulp of the fruit of C. microphylla (4.85%), originating in the xerophytic Monte in Northern Patagonia, whose values were higher than those reported for Z. mauritiana grown in the fertile plains of Bangladesh (i.e., 0.85%-1.2%) [24].…”
Section: Analysis Of Phytonutrients In C Microphyllacontrasting
confidence: 49%
“…The proteins present in the mesocarp of fleshy fruits tend to be associated with the metabolic processes of the plant, environment and the stress of pathogen exposure. When plants are subjected to different environmental stresses, qualitative and quantitative changes in the protein content occur [23]. This phenomenon could explain the levels of total proteins found in the pulp of the fruit of C. microphylla (4.85%), originating in the xerophytic Monte in Northern Patagonia, whose values were higher than those reported for Z. mauritiana grown in the fertile plains of Bangladesh (i.e., 0.85%-1.2%) [24].…”
Section: Analysis Of Phytonutrients In C Microphyllacontrasting
confidence: 49%
“…Compatible solutes (Lauxmann et al 2014), cell walls (Brummell et al 2004a;Gonzalez-Aguero et al 2008), carbohydrates (Nilo et al 2010;Wang et al 2013), energy substrates (Nilo et al 2010), phytohormones (Zhou et al 2001;Dagar et al 2012), transcriptional regulation (Puig et al 2015) as well as cold defense proteins (Dagar et al 2010) have been proposed to be linked with peach fruit CI. In addition, data from genome-wide analysis have suggested that comprehensive and fine metabolic adjustments as well as complicated regulation are involved in postharvest peach CI (Vizoso et al 2009;Nilo et al 2010;Chan 2013;Pons et al 2014;Pegoraro et al 2015;Puig et al 2015;Sanhueza et al 2015). However, very little is known about the early events involved in the response to cold and the regulatory mechanisms that operate at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was also proposed that CTG134 gene, a precursor of a peptide hormone of the RGF/GLV, regulates ethylene-auxin cross-talk during peach fruit ripening (Tadiello et al, 2016). Given that the proteome is closer to the fruit phenotype than is the genome or the transcriptome along with the fact that it is more directly responsive to environmental stimuli (Chan, 2012), proteomic analysis provides a comprehensive view of fruit's adaptation to different environments. Almost all past proteomic studies of peach fruit were focused on mesocarp tissue (Lara et al, 2009; Nilo et al, 2010, 2012; Hu et al, 2011; Prinsi et al, 2011; Zhang et al, 2011; Giraldo et al, 2012); whereas research concerning skin proeome as an isolated component during peach ripening have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%